IMPACT OF FINANCIAL TECHNOLOGY (FINTECH) ON SHARIA BANKING: PERSPECTIVE OF FIQH ECONOMIC - Nisaa, Mufida Auliyaun; Yazid, Muhammad; Abdelmagid, Eltayeb Salah Eltayeb (Ekonomi Islam, 2024)
The research was conducted with the aim of ensuring that sharia banking customers can be more confident and careful in using financial technology in carrying out sharia banking activities. This research is qualitative research with a literature review research method, namely a method of reviewing research that has been carried out previously which relies on various relevant books or journals. It can be concluded that according to the perspective of fiqh economic, the financial technology (fintech) used in sharia banking is a form of adaptation to technological advances from time to time. Due to technological advances, human needs are also progressing and becoming more diverse. So that the existence of financial technology is relevant to the perspective of fiqh economic in terms of realizing benefits for humanity in accordance with the maqashid of sharia. Customers must of course understand more about sharia principles in the Fintech sector, including rukun, contracts, provisions, law, tax administration, accounting and audit, in order to avoid usury and gharar.